Induction and Suppression of Innate Antiviral Responses by Hepatitis A Virus - Cao, Xin; Xue, Yu-jia; Du, Jiang-long; Xu, Qiang; Yang, Xue-cai; Zeng, Yan; Wang, Bo-bo; Wang, Hai-zhen; Liu, Jing; Cai, Kui-zheng; Ma, Zhong-ren (Frontiers in Microbiology, 2018)
Hepatitis A virus (HAV) belongs to the family Picornaviridae. It is the pathogen of acute viral hepatitis caused by fecal-oral transmission. RNA viruses are sensed by pathogen-associated pattern recognition receptors (PRRs) such as Toll-like receptor 3 (TLR3), retinoic acid-inducible gene I (RIG-I), and melanoma differentiation-associated gene 5 (MDA5). PRR activation leads to production of type 1 interferon (IFN-α/β), serving as the first line of defense against viruses. However, HAV has developed various strategies to compromise the innate immune system and promote viral propagation within the host cells. The long coevolution of HAV in hosts has prompted the development of effective immune antagonism strategies that actively fight against host antiviral responses. Proteases encoded by HAV can cleave the mitochondrial antiviral signaling protein (MAVS, also known as IPS-1, VISA, or Cardif), TIR domain- containing adaptor inducing IFN-β (TRIF, also known as TICAM-1) and nuclear factor-κB (NF-κB) essential modulator (NEMO), which are key adaptor proteins in RIG-I-like receptor (RLR), TLR3 and NF-κB signaling, respectively. In this mini-review, we summarize all the recent progress on the interaction between HAV and the host, especially focusing on how HAV abrogates the antiviral effects of the innate immune system.